An integrated method for landscape assessment: application to Santiago de Cuba Bay, Cuba (2021)
Human activities often drive landscape degradation and the associated loss of value. This paper describes a method that, by integrating multiple factors, characterize landscape value to establish relevant and effective management practices. The new integrated method for landscape assessment (IMLA) is a four-step model that includes: (i) establishment of a general theoretical basis for sustainability relevant metrics; (ii) characterization of the landscape; (iii) landscape valuation; (iv) recommendations for landscape value management. Each step includes different interactive components of analysis. The new IMLA considers the potential range of values associated with each landscape unit and facilitates sustainable landscape management. The method is systematic and includes both inductive and deductive reasoning. Its articulation is represented in the conjunction and overlapping of all factors and variables considered. IMLA was tested in Santiago de Cuba Bay (Cuba) and used to determine five landscape scopes, eight first-order landscape units and 29 s-order units. It proved to be a useful tool to establish landscape values and sound management strategies. Application of IMLA in Cuba will help local authorities institute land-use plans and to establish decision-making processes that include valuation of cultural landscapes.